Islam di Malaysia dan sastera Nusantara - Hamzah Hamdani, 1953-; Seminar Tak'kan Hilang Melayu di Dunia 2004 : Indramayu, Indonesia). (Kuala Lumpur : Gapeniaga, 2005)
Issues on Islam in Malaysia and Malay literature.
Koleksi Sumbangan : Abdul Ghafar Ibrahim
Includes bibliographical references.
Keywords: Islam -- Malaysia; Islam and literature